Dampak Program Pengembangan Pelatihan terhadap Kinerja Perawat RSIJ Cempaka Putih dengan Model Pendekatan System Dynamics - Budi Hartono; Nisa Afriza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to see how much the nurse development program of the Jakarta Cempaka Putih Islamic Hospital has the potential to influence the performance of nurses at the Cempaka Putih Islamic Hospital. The research method used in this research is to use the Dynamic System Approach (System Dynamics). The results of modeling using historical data show that the training development program in the long term shows a decrease so that it has an impact on the performance of nurses which also shows decreased behavior while the results of modeling based on simulations show a significant increase in nurse performance if an increase in the policy target hours of the nurse training development program is based on target hours from HPMI. In conclusion, the performance of nurses at RSIJ Cempaka Putih actually shows decreased behavior, which is different from the performance reported based on the Key Performance Indicator (KPI) and Performance Appraisal that the dominant nurse's performance is up to standard. Keywords: Performance, Competence, Training Motivation, System Dynamics